The Influence of Perfectionism Personality Towards Dyadic Coping within Marriage - Siti Nurraihan Firdaus Binti Abdul Razak; Suzana Mohd Hoesni; Rozmi Ismail; Ezarina Zakaria (Asian Social Work Journal, 2016)
Divorce and the collapse of marital institutions are global issues which draws attention from many parties. As a result of the existence of quality family being a catalyst in the development of society, emphasis should be made to aspects of coping among married couples, especially during handling arising stress. Results show that research relating to dyadic coping within marriage has gradually gained attention from researchers. Many previous research indicate that personality has been a contributing factor in determining the actions taken by an individual. However, previous research has focused more on the five big traits compared to other types of personality such as perfectionism. Previous research has proved the existence of relationship between perfectionism personality with other aspects of life especially mental health and marital satisfaction. On the other hand, how much perfectionism personality influence dyadic coping within marriage still remains a question. Hence, this conceptual paper will discuss on the potential of perfectionism personality influence dyadic coping based on previous research. Eventually, implication and the importance of this study will also be discussed in the effort to encourage married couples to apply effective coping while retaining a harmonious marriage.